Novel Heterocyclic Fused Pyarzolequinolines: An Efficient Synthesis, DNA Binding Interaction and Antimicrobial Activity - Lamani , Devappa S. (Novel Aspects on Chemistry and Biochemistry Vol. 6, 2023)
This chapter reported a rapid and efficient method for the synthesis of novel fused- pyarzolequinolines derivatives in acetic acid aqueous media with quantitative yield. The synthesized compounds (2a) and (4a) interact with CT-DNA. Fused tetracyclic systems containing a quinoline nucleus represent an important class of heterocyclic bioactive natural products and pharmaceuticals because of their significant and wide-spectrum biological properties. Several of these compounds have been obtained with diverse pharmacological and biological activities, such as antiplasmodial, antifungal, antibacterial, potent antiparasitic, antiproliferative, anti-tumor and anti-inflammatory activities. In the present chapter, the synthesis of 3-(5-phenyl-4,5-dihydro-1H-pyrazol-3-yl)quinolin-2-ol (2a)/(3a) and 3-(2-hydroxyquinolin-3-yl)-5-phenyl-4,5-dihydro-1H-pyrazole-1 carbothioamide(4a) were prepared according to Claisen-Schmidt condensation, via condensation of 2- hydroxyquinoline-3-carbaldehyde with ketones. All organic solvents used for the synthesis were of analytical grade. The TLC was performed on Baker-Flex silica gel 1B-F (1.55) plates using ethyl acetate and petroleum ether. Then finally, a, Q-unsaturated ketone (3) reacts with hydrazine hydrate, phenylhydrazine and thiosemicarbazide obtained from the corresponding substituted fused-pyarzolequinolines. The proposed structures of the products and characterizations synthesized compounds of the reactions were assured based on the spectral data and chemical evidences. Viscosity experiment is considered as one of the least ambiguous and the most critical tests of a binding mode in solution in the absence of crystallographic structure data. The newly synthesized compounds were characterized by elemental analysis, IR, 1H-NMR, and Mass spectral data. The interaction of the chosen chemicals with calf thymus-DNA (CT-DNA) was investigated utilizing electronic spectra, viscosity tests, and thermal denaturation studies. The absorbance spectrum experienced bathochromic and hypochromic alterations upon binding to CT-DNA. The binding constant (Kb) gave value of 5.3x104 M-1 for (2a) and 6.5x105 M-1 for (4a). The viscosity measurements indicated that the viscosities of sonicated rod like DNA fragments were increased. The newly synthesized compounds tested for antimicrobial activity and, from protocol shows sulfur containing carbothioamide compounds (4a) exhibited significant inhibitory activity and also bind more strongly with calf thymus-DNA compared to (2a).